FROM THE EDITOR’S DESK - Dr. Fatema Jawad (Journal of the Pakistan Medical Association, 2024)
We enter the New Year 2025 with hopes and expectations for more achievements by our Journal of Pakistan Medical Association. It has been a very busy past 2024, with increasing number of submissions, which amounts to excessive work for all at the office. We have published Ten National Supplements, mostly Guidelines and Two supplements from abroad. The work in the journal office has rather been in the form of policing or catching thieves. The standard of Ethics has unfortunately receded in the authors. We are detecting more of plagiarized articles, redundant submissions, gifted/ unauthorized authorship, wrong or tampered IRB Approval Letters and sliced articles. It is unfortunate, but the pressure to publish by the regulatory bodies, takes its toll. In the present times, most students or senior doctors are not very keen to write research. At times paid help is acquired, which can be expensive and not reliable. Undergraduate students want to publish which gets them opportunities to work abroad. It seems most of the youngsters desire to travel to the UK or USA for higher studies as they believe that there are more opportunities in these countries for a better life. It only proves the disappointments faced in our own country, which we experience very frequently. The government, the regulatory bodies and the senior faculty has the responsibility of creating better and favourable opportunities for the younger generation, who will be the future health care providers for the people of Pakistan. I would like to state a few words of gratitude to the colleagues who have been a pillar of strength in assisting with the editorial responsibilities of JPMA. Dr. Anwar Siddiqui has shouldered the major load. Dr. Mubeen, Dr. Sina Aziz and the recently inducted Dr. Umair Sami are the regular members of the core team. Ms. Maria Najam and Rizwana, help out with the technical review of the case reports, whereas Mr. Humair takes care of the Research and Review articles. Thanks are due to all of them. The office of JPMA is always humming with work. It is lead by Mr. Abdul Majid and the other responsible staff who assist him include, Mr. Adil, Mr. Faizan, Mr. Munib, Mr. Ghaffar and Mr. Ramzan. It would not be possible to have the present efficiency without their dedicated services. I take this opportunity to thank all our learned peer reviewers and stats reviewers for their help and assistance. The Special Section is a unique part of the journal for which the section editors hold the responsibility. Dr. Sanjay Kalra from Karnal, India, organizes the latest information on Primary Care Diabetes, Advances in Endocrinology and Barocrinology. Dr. Shahzad Shamim from Karachi, is the section editor for Neurooncology, Dr. Farooq Rathore from Islamabad, is responsible for the Rehabilitation section and Dr. Aamna Hassan from Lahore takes care of the IMAGES Section. My gratitude is extended to all of them. Last but not the least are our readers. JPMA is widely read and very often we get comments which are published in the forthcoming issues. I am full of thanks to our readership from all over the world. I end here with all good wishes for the New Year 2025 to all connected with JPMA. My Prayers are for the entire community linked with JPMA. May we have better days in the coming year. We complete 75 years of publication in 2025 and have grown. May the Almighty Bless us with more success.